Attitudes towards Gender Equality and the Representation of Women in Parliament: A comparative study of South Africa, Uganda and Zimbabwe - Jacobs, Chantal; Jacobs, Chantal Rowena (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Political Science))--University of Stellenbosch, 2009.